SIMULATION MODEL OF THE PRODUCTIVITY OF A HERD OF GOATS GRAZING UNDER DIFFERENT SCENARIOS OF HANDLING IN THE SOUTHWESTERN REGION OF TAMAULIPAS, MEXICO - A. Villanueva-Castillo; J. C. MartÃnez-GonzÃ¡lez; H. DÃaz-SolÃs; W. E. Grant; A. Moreno-ValdÃ©s; J. M. Tapia-GonzÃ¡lez; R. S. Moreno-MejÃa (Tropical and Subtropical Agroecosystems, 2013)
One of the major current challenges in the livestock industry is meeting the demand for livestock products of a growing world population. Bio-economic models integrate animal biology and rural enterprise management, which allows for the study of complex animal production systems. This paper aims at simulating the productive performance of a herd grazing under different management conditions. To do so, a simple simulation model of a goat herd (MSSRC), rangeland forage growth, and the dynamics of animal population in the semi-arid region of Southwestern Tamaulipas under three rainfall scenarios (300, 500, and 700 mm. of average annual precipitation) was built. The objective was to evaluate the sustainability of extensive grazing under different animal loads. Nine different scenarios were evaluated, corresponding to the different combinations of the three rainfall scenarios and three levels of initial loads (Hi) and nannies maximum load (HMAX). Evaluated variables are: kids sales (C); total number of nannies (female goats, HT); sales of replacement nannies (VREE); sales of scrap goats (CDS); rangeland condition (CA); voluntary consumption (CV); mortality rate (M); abortion rate (A); and average annual profits (UPA). Simulation was performed on a 1,000 hectares plot, and three 10-year periods were used as time framework. Analysis of Variance (ANOVA) revealed statistically significant (P < 0.05) differences between scenarios for all studied variables. Biomass primary net production under the 300, 500, and 700 mm of rainfall was found to be 1,132.2 ± 362.9, 2,244.2 ± 517.0, and 3,113.3 ± 598.7 kg DM ha-1 per year, and the average annual production of kids was 36 ± 17, 90 ± 31, and 132 ±37, respectively. The low loads scenarios showed a stable behavior, with a constant rate of kids production over the three simulation periods (0-30 years), which resulted in a higher average annual profit, and a more sustainable profile than those with heavier loads. The proposed simulation model is a good tool for decision-making in the management of extensive grazing in natural rangelands. The model and its results improve managers’ abilities to analyze and implement required measures to increase productive efficiency.